PEMBERDAYAAN EKONOMI PESANTREN MELALUI PENGEMBANGAN KOPERASI - Santi Rahmawati (IZZI: Jurnal Ekonomi Islam, 2022)
The purpose of this study was to determine the management model of the Islamic boarding school cooperative business unit as a form of economic independence. This research method uses descriptive qualitative research methods and uses a type of case study research. The object of this research is the women's cooperative. Data were collected using direct interviews with three informants, consisting of the Head of the Kopontren, the Head of the Business Unit, and the Kopontren's Management (Kasir). The Al-KhairiyahIslamic boarding school is able to improve the economy of the pesantren by developing business units in the pesantren without outside assistance such as the women's cooperative business unit in this pesantren. In every industry, a management strategy is needed so that it can develop properly, in Kopontren not only employees who play a role in the industry but the head of supervision from the caregivers and the head of the unit so that the business unit achieves effectiveness and efficiency of the Al-KhairiyahIslamic boarding school which is able to improve the economy of the pesantren by developing business units. existing in the pesantren without outside assistance such as the women's cooperative business unit in this pesantren.